Crowdfunding Research: Critical Analysis and Constructive Agenda for Future Inquiry - Swati Oberoi; Rohit Joshi
Crowdfunding (CF), an innovative entrepreneurial phenomenon, has gained considerable attention in social science outlets. Yet, the overall intellectual structure of this growing field of enquiry remains under wraps. This study addresses this knowledge gap by critically analysing 534 published articles using co-citation analysis of influential CF publications and tracing the intellectual history of the four variants of CF, namely rewards, donation, debt and equity. The co-citation analysis of highly cited publications uncovers the DNA (dynamics, nuances and anchors) of CF research revealing the field$1 (Bs underlying disciplines and its theoretical anchors. Overall, the authors take cognisance of the intellectual scaffolding of CF research, map the advancement of CF variants and recognise its potential to act as a force of social and economic disruption. The critical analysis reported here reveals gaps in the extant literature which can provide novel avenues for productive enquiry by future CF scholars.s